PERAN PEREMPUAN PENYINTAS DALAM PROSES RECOVERY PASCA BENCANA ERUPSI GUNUNG SEMERU DI DESA SUMBERMUJUR LUMAJANG - Isom Maulan Safi’i (Universitas Baturaja, 2023)
This study aims to define the role of women survivors in the recovery process after the eruption of Mount Semeru in Sumbermujur Lumajang Village. As we know, women in this condition are in a very risky and vulnerable condition. However, in an emergency situation, women are able to play an important role, especially in their family, in the post-disaster recovery process. So as to be able to provide healing for trauma and strengthening for their children and husbands.